Cost-effectiveness of ranibizumab and bevacizumab for age-related macular degeneration: 2-year findings from the IVAN randomised trial. Issue 7 (29th July 2014) - Dakin, Helen A; Wordsworth, Sarah; Rogers, Chris A; Abangma, Giselle; Raftery, James; Harding, Simon P; Lotery, Andrew J; Downes, Susan M; Chakravarthy, Usha; Reeves, Barnaby C; ,
Abstract : Objective: To assess the incremental cost and cost-effectiveness of continuous and discontinuous regimens of bevacizumab (Avastin) and ranibizumab (Lucentis) for neovascular age-related macular degeneration (nAMD) from a UK National Health Service (NHS) perspective. Design: A within-trial cost-utility analysis with a 2-year time horizon, based on a multicentre factorial, non-inferiority randomised controlled trial. Setting: 23 hospital ophthalmology clinics. Participants: 610 patients aged ≥50 years with untreated nAMD in the study eye. Interventions: 0.5 mg ranibizumab or 1.25 mg bevacizumab given continuously (monthly) or discontinuously (as-needed) for 2 years. Main outcome measures: Quality-adjusted life-years (QALYs). Results: Total 2-year costs ranged from £3002/patient (4700; 95% CI £2601 to £3403) for discontinuous bevacizumab to £18 590/patient (29 106; 95% CI £18 258 to £18 922) for continuous ranibizumab. Ranibizumab was significantly more costly than bevacizumab for both continuous (+£14 989/patient (23 468); 95% CI £14 522 to £15 456; p<0.001) and discontinuous treatment (+£8498 (13 305); 95% CI £7700 to £9295; p<0.001), with negligible difference in QALYs. Continuous ranibizumab would only be cost-effective compared with continuous bevacizumab if the NHS were willing to pay £3.5 million (5.5 million) per additional QALY gained. Patients receiving continuous bevacizumab accrued higher total costs (+£599 (938); 95% CI £91 to £1107; p=0.021) than those receiving discontinuous bevacizumab, but also accrued non-significantly more QALYs (+0.020; 95% CI −0.032 to 0.071; p=0.452). Continuous bevacizumab therefore cost £30 220 (47 316) per QALY gained versus discontinuous bevacizumab. However, bootstrapping demonstrated that if the NHS is willing to pay £20 000/QALY gained, there is a 37% chance that continuous bevacizumab is cost-effective versus discontinuous bevacizumab. Conclusions: Ranibizumab is not cost-effective compared with bevacizumab, being substantially more costly and producing little or no QALY gain. Discontinuous bevacizumab is likely to be the most cost-effective of the four treatment strategies evaluated in this UK trial, although there is a 37% chance that continuous bevacizumab is cost-effective. Trial registration number: ISRCTN92166560.